Response of plasma pancreatic and gastrointestinal hormones and growth hormone to oral and intravenous glucose and insulin hypoglycaemia in Chagas's disease. Issue 9 (September 1980) - Long, R G; Albuquerque, R H; Prata, A; Barnes, A J; Adrian, T E; Christofides, N D; Bloom, S R
Abstract : Plasma hormonal responses to insulin hypoglycaemia and to oral and intravenous glucose were investigated in chagasic patients with severe bowel disease and compared with controls matched for age, sex, weight, and race. After intravenous insulin, plasma concentrations of pancreatic glucagon and pancreatic polypeptide (PP) were reduced in the patients with Chagas's disease. These subjects also showed a subnormal rise in plasma insulin after oral glucose. Other hormone responses did not differ significantly from those in the normal controls. These results are compatible with partial denervation of the pancreatic alpha, beta, and PP cells in patients with chronic gastrointestinal Chagas's disease.